Respiratory viruses in young South African children with acute lower respiratory infections and interactions with HIV - Annamalay, A.; Abbott, S.; Sikazwe, C.; Khoo, S.; Bizzintino, J.; Zhang, Guicheng; Laing, I.; Chidlow, G.; Smith, D.; Gern, J.; Goldblatt, J.; Lehmann, D.; et al. (Elsevier, 2016)
© 2016 Elsevier B.V..Background: Human rhinovirus (RV) is the most common respiratory virus and has been associated with frequent and severe acute lower respiratory infections (ALRI). The prevalence of RV species among HIV-infected children in South Africa is unknown. Objectives: To describe the prevalence of respiratory viruses, including RV species, associated with HIV status and other clinical symptoms in children less than two years of age with and without ALRI in Pretoria, South Africa. Study design: Nasopharyngeal aspirates were collected from 105 hospitalized ALRI cases and 53 non-ALRI controls less than two years of age. HIV status was determined. Common respiratory viruses were identified by PCR, and RV species and genotypes were identified by semi-nested PCR, sequencing and phylogenetic tree analyses. Results: Respiratory viruses were more common among ALRI cases than controls (83.8% vs. 69.2%; p = 0.041). RV was the most commonly identified virus in cases with pneumonia (45.6%) or bronchiolitis (52.1%), regardless of HIV status, as well as in controls (39.6%). RV-A was identified in 26.7% of cases and 15.1% of controls while RV-C was identified in 21.0% of cases and 18.9% of controls. HIV-infected children were more likely to be diagnosed with pneumonia than bronchiolitis (p < 0.01). RSV was not identified in any HIV-infected cases (n = 15) compared with 30.6% of HIV-uninfected cases (n = 85, p = 0.013), and was identified more frequently in bronchiolitis than in pneumonia cases (43.8% vs. 12.3%; p < 0.01). Conclusions: RV-A and RV-C are endemic in South African children and HIV infection may be protective against RSV and bronchiolitis.